Pre-suasion : a revolutionary way to influence and persuade - Cialdini, Robert B. (Simon & Schuster, 2016)
Examines the art of effective persuasion to argue that its secret lies in a key moment before messages are delivered, sharing strategies for how to psychologically prepare one's listeners to render them most receptive.